Effect of elevated ozone and carbon dioxide on growth and yield of rice (Oryza sativa) - KUMAR, RAM; BHATIA, ARTI; CHAKRABARTI, B; KUMAR, V; TOMER, R; SHARMA, D K; KUMAR, SOORA NARESH (The Indian Journal of Agricultural Sciences, 2021)
An experiment was conducted by growing Pusa 44 rice (Oryza sativa L.) variety under different treatments: Ambient, Elevated O3 (EO3: 60 ± 10 ppb), Elevated CO2 (ECO2: 550 ± 10 ppm) and Elevated CO2 and O3 (550 ± 10 ppm CO2 and 60 ± 10 ppb EO3) in free air carbon dioxide and ozone enrichment facility (FACE-O3) with the objective to assess the impact of elevated tropospheric ozone (O3) and carbon dioxide (CO2) interaction on growth and yield of rice. The crop was exposed to elevated levels of gases from transplanting to maturity. EO3 was found to be having a negative impact on all the growth parameters at vegetative, anthesis and maturity stages. ECO2 was found to be having a compensatory effect over EO3 for the different growth parameters. On an average the compensatory effect of ECO2 over EO3 on yield was about 40% and negative impact of elevated O3 over control was around 26% in both the years.